"White picket fences" : lesbians' narratives of kinship building with their sisters in Newfoundland and Labrador - Fitzpatrick, Laura, 1971- (2002)
Thesis (M.W.S.)--Memorial University of Newfoundland, 2003. Women's Studies Programme Bibliography: leaves [123]-147.